The Critical Situation: Vexed Perspectives in Postmodern Literary Studies. - Schreier, Benjamin (Journal of Modern Literature)
Robert T. Tally, Jr.'s 2023 book The Critical Situation: Vexed Perspectives in Postmodern Literary Studies, a collection of previously published essays, offers a remarkably coherent picture of post-Americanist critical agency with theoretical sophistication, political savvy, and humanist good humor. Spoiler alert: the bad guys are those who with self-satisfaction embrace what can be generalized under the banner of "post-theory."